Integrasi Potensi Wisata Desa dan UMKM Berbasis Budaya menuju Desa Mandiri Budaya di Kalurahan Wirokerten, Kabupaten Bantul - Sakir, Sakir; Pribadi, Ulung; Dyah Mutiarin; Kadek Primayudi; Nursetiawan (Warta LPM, 2025)
The many potentials of culture tourism and the MSME economy in Wirokerten Village provide opportunities for the realization of Wirokerten Village as a Cultural Independent Village. However, from the many potentials owned, Wirokerten Village still has challenges and problems, namely the need for institutional solid management in integrating tourism potential and not optimizing the marketing of culture-based tourism-MSME potential in Wirokerten Village. The purpose of this activity is to optimize marketing and strengthen institutional management in integrating the tourism potential of culture-based SMEs in Wirokerten Village. The method used in this service is the Asset Based Community Development (ABCD) approach, which is empowerment that aims at community development by emphasizing the potential or assets in a group or region. The results of this program are the formation of a decree on the formation of Pokdarwis, a decree on the Tourism Village Manager, a decree on the Village-Owned Business Entity (BUMKal), Ngontel Ndeso & Ngandong Ndeso Tourism Packages, a cultural-based branding concept for the Pasar Blumbang Mataraman, and an increase in community understanding based on Go-Digital MSMEs. This activity is expected to lead Wirokerten Village to become a Village with the title of Cultural Independent Village.